Kajian Psikologi Tokoh Sastra ring Satua cutet I Kucil, Idup Lara, Turmaning Pajalan Keneh ring Sajeroning Buku Nimbang Rasa (Pusat riset dan Inovasi Nasional, 2026)
This study aims to describe the intrinsic structure and analyze the psychological aspects of the main characters in the three short stories based on Sigmund Freud's psychoanalytic theory. The research uses a qualitative approach with descriptive methods. Data sources are texts from three satua cutet in the Nimbang Rasa anthology: I Kucil by I Komang Tri Nanda Defhayana, Idup Lara by Ni Wayan Esa Juliantini, and Pajalan Keneh by Ni Putu Ayu Ari Astiti. Results show that the intrinsic structure of all three stories employs a linear plot, with themes of diligence, perseverance, and courage. Psychological analysis based on Freud's id, ego, and superego theory reveals that I Kucil is dominated by id impulses in the form of aggressive emotion due to injustice; Ani demonstrates a strong ego in withstanding social pressure and a firm superego in upholding moral values; while Gékyu shows a balance between ego and superego when facing abuse from a teacher. This research is expected to serve as a reference in Balinese literary studies, particularly in the field of literary psychology.